Testiranje modelov VaR v izjemnih okoliščinah - Žunko, Matjaž (IB revija (Ljubljana), 2011)
In this article, we review various VaR approaches and derive the pros and cons of each methodology in terms of time horizon, complexity, resources, level of reporting, and specific needs (for example, regulatory requirements). In our view, the risk management process should not rely heavily on VaR calculations, since they may quite often underestimate risk. This may seem like a controversial statement, but VaR is only valid under normal market conditions and with a series of theoretical assumptions. Therefore, it must always be interpreted within this set of assumptions. That is something that most VaR critics forget too easily.
Keywords: trg vrednostnih papirjev; vrednost; tveganje; testiranje; metode; simulacija